EXTH-59. INTRACRANIAL IMPLANTATION OF TUMORICIDAL STEM CELL-SEEDED SCAFFOLDS AFTER GLIOBLASTOMA RESECTION. (5th November 2018) - Sheets, Kevin; Rodriguez-Bago, Juli; Paulk, Ivory; Hingtgen, Shawn
Abstract: The most common and aggressive primary brain cancer, glioblastoma (GBM), carries a life expectancy of 12–15 months. The short life expectancy is due, in part, to the inability of the current treatment, consisting of surgical resection followed by radiation and temozolomide, to eliminate invasive tumor foci. Treatment targeting invasive tumor foci may be advanced with tumoricidal human mesenchymal stem cells (MSCs). These cells exhibit potent tumor tropism and can be engineered to kill tumor cells in preclinical models. Advancements in preclinical models indicate surgical resection induces premature MSC loss and reduced therapeutic efficacy. Efficacy of MSC treatment can be improved by preloading MSCs on a biodegradable poly(lactic acid) (PLA) scaffold. MSC delivery on a PLA scaffold restores cell retention, persistence, and tumor killing. To study the effects of MSC-seeded PLA implantation on GBM, an accurate preclinical model is needed. Here we report a preclinical surgical method for performing image-guided tumor resection of GBM in immune-deficient mice followed by MSC-seeded scaffold transplantation. MSCs were engineered with lentiviral constructs to constitutively express and secrete the DR4/5 agonist TNFα-related apoptosis inducing ligand (TRAIL) as well as GFP to allow fluorescent tracking. Similarly, the human GBM tumor cells were engineered to express mCherry and Firefly luciferase, providing dual fluorescent/luminescent tracking capabilities. Using quantitative BLI, we found that maximal resection of visible fluorescent tumor cells failed to fully eradicate the tumor mass. Up to 10% of the pre-operative tumor signal intensity remained post-resection, mirroring observations in human patient testing. MSC-TRAIL implanted on PLA scaffolds were found to significantly suppress tumor recurrence, as animal survival improved 120% over control (13.5 vs 31 days). While used currently for investigating improvements to stem cell mediated delivery of therapeutics, this approach could be modified to research the impact of surgical resection on other therapeutic interventions.